Impact of AR-supported STEAM based project learning on students’ numeracy skills: A meta analytic - Annisa, Herwayuninda; Muhtarom; Dwijayanti, Ida (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to examine the overall effectiveness of AR-supported STEAM based Project Based Learning (PjBL) in improving students’ numeracy skills through a comprehensive synthesis of empirical research. Method: A quantitative meta-analysis was conducted to aggregate findings from 25 national and international experimental and quasi-experimental studies published between 2019 and 2025. Eligible studies were selected using predefined inclusion criteria focusing on interventions combining PjBL, STEAM, and Augmented Reality in mathematics learning contexts. Effect sizes were computed using Cohen’s d and analyzed under a random effects model to account for variability across studies. Findings: The analysis produced a pooled effect size of 0.85, which falls within the high-impact category. These findings indicate that AR-supported STEAM PjBL consistently yields stronger numeracy outcomes compared to conventional instructional approaches. The integration of immersive Augmented Reality visualization within contextualized STEAM projects appears to support conceptual clarity, particularly in abstract mathematical topics, while simultaneously fostering active engagement and meaningful learning experiences. Significance: This study provides consolidated empirical evidence supporting the pedagogical potential of AR-integrated STEAM project learning in mathematics education. The results offer evidence-based implications for educators, curriculum developers, and policymakers seeking scalable strategies to strengthen numeracy literacy in technology-enhanced learning environments.